(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
A 35 years old lady was admitted to Square Hospital for termination of pregnancy on a medico-legal background. She was a diagnosed case of carcinoma of pancreas with Whipples operation performed six months back and was on chemotherapy. During pre-operative check-up we surprisingly noticed that she has Bombay Blood Group. It is a very rare type of blood group and on routine blood grouping behaves as O unless reverse grouping or serum grouping has been done and can receive transfusion from only peoples having Bombay group. As the patients general condition was poor and had recently received chemotherapy and also had a extremely rare blood group ((I in 250000) we decided to keep ready one unit of blood. We decided to provide autologus blood transfusion, as there was no known person in family or in our blood banks record with Bombay Blood Group. The procedure was uneventful and needed no transfusion. As the patient was anaemic and weak, we decided to transfuse the blood in the post-operative period and the patient was discharged from the hospital next day morning. DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18157 Journal of BSA, 2010; 23(1): 34-36